2015
DOI: 10.1155/2015/189872
|View full text |Cite
|
Sign up to set email alerts
|

Dental Stem Cell Migration on Pulp Ceiling Cavities Filled with MTA, Dentin Chips, or Bio-Oss

Abstract: MTA, Bio-Oss, and dentin chips have been successfully used in endodontics. The aim of this study was to assess the adhesion and migration of dental stem cells on human pulp ceiling cavities filled with these endodontic materials in an experimental model, which mimics the clinical conditions of regenerative endodontics. Cavities were formed, by a homemade mold, on untouched third molars, filled with endodontic materials, and observed with electron microscopy. Cells were seeded on cavities' surface and their mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
1
6
0
2
Order By: Relevance
“…As shown in Figs 3 and 4 , Exp promoted cellular migration and adhesion. Our findings are in agreement with previous studies showing that MTA could accelerate the migration and adhesion of dental pulp-derived cells 35 36 . A migration assay also provided the first in vitro evidence of a similar migration effect of PC on hDPSCs, but Vincenzo et al 37 found that MTA enhances HMSC migration significantly more than PC.…”
Section: Discussionsupporting
confidence: 94%
“…As shown in Figs 3 and 4 , Exp promoted cellular migration and adhesion. Our findings are in agreement with previous studies showing that MTA could accelerate the migration and adhesion of dental pulp-derived cells 35 36 . A migration assay also provided the first in vitro evidence of a similar migration effect of PC on hDPSCs, but Vincenzo et al 37 found that MTA enhances HMSC migration significantly more than PC.…”
Section: Discussionsupporting
confidence: 94%
“…The results of this study showed that extracts from Bioroot BC Sealer, Endoseal MTA and Nano-ceramic Sealer had dose-and time-dependent effects on the biological responses of hPDLSCs. Due to the excellent properties of mineral trioxide aggregate (MTA), new endodontic materials based on MTA have emerged recently (Bin et al 2012, Butt et al 2014, Zhu et al 2014, Lymperi et al 2015, Utneja et al 2015. However, the different compositions of MTA sealers are often unknown, and sealers have provided differing results for their biocompatibility in vitro and in vivo (G€ uven et al 2013(G€ uven et al , Chang et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Данные о цитотоксическом влиянии на SHED костно-пластических материалов, содержащих ксеногенный ГА, соотносятся с результатами других исследований последних лет. Так, было показано, что миграция ММСК пульпарного происхождения в материал Bio-Oss происходит значительно менее интенсивно по сравнению с МТА-цементом и гранулированным дентином [13].…”
Section: Discussionunclassified